The potential for emerging therapeutic options for Clostridium difficile infection - Mathur, Harsh (Gut Microbes, 2015)
Clostridium difficile is mainly a nosocomial pathogen and is a significant cause of antibiotic-associated diarrhea. It is also implicated in the majority of cases of pseudomembranous colitis. Recently, advancements in next generation sequencing technology (NGS) have highlighted the extent of damage to the gut microbiota caused by broad-spectrum antibiotics, often resulting in C. difficile infection (CDI). Currently the treatment of choice for CDI involves the use of metronidazole and vancomycin. However, recurrence and relapse of CDI, even after rounds of metronidazole/vancomycin administration is a problem that must be addressed. The efficacy of alternative antibiotics such as fidaxomicin, rifaximin, nitazoxanide, ramoplanin and tigecycline, as well as faecal microbiota transplantation has been assessed and some have yielded positive outcomes against C. difficile. Some bacteriocins have also shown promising effects against C. difficile in recent years. In light of this, the potential for emerging treatment options and efficacy of anti-C. difficile vaccines are discussed in this review.